How health motivation moderates the effect of intention and usage of wearable medical devices? An empirical study in Malaysia - Hayat, Naeem; Zainol, Noor Raihani; Salameh, Anas A.; Al Mamun, Abdullah; Yang, Qing; Md Salleh, Mohd Fairuz (Frontiers in Public Health, 2022)
Mobile technology is popular because it facilitates users in multiple ways. This technology is revolutionising the healthcare industry, and mobile-based wearable medical devices (WMDs) are becoming common. Technology adoption is always challenging, and technology value is based on the technology attributes and personal inclination towards using the technology. This study investigates how the perceived product value is influenced by compatibility, cost, personal privacy, technology accuracy, and usefulness. The perceived product value instigates the intention to use wearable medical devices and health motivation (HMT), and the intention to use promotes the adoption of WMDs. Furthermore, the relationship between the intention to use and the adoption of WMDs is moderated by HMT. The current work employed a cross-sectional research design, and data were collected through an online survey of Malaysian adults. Data analysis was performed using partial least squares structural equation modelling (PLS-SEM). The analysis revealed that the WMDs’ compatibility, cost, and technology accuracy significantly influenced the WMDs’ value. Besides, the perceived product value impacted the intention to use WMDs, while HMT and intention to use WMDs insignificantly influenced the adoption of WMDs. Finally, HMT significantly moderated the relationship between the intention to use and the adoption of WMDs. This study also reports the limitations and future research opportunities.